2018
DOI: 10.1016/j.neuropharm.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue oxygen regulation in awake and anesthetized neonates

Abstract: Inhaled general anesthetics are used commonly in adults and children, and a growing body of literature from animals and humans suggests that exposure to anesthesia at an early age can impact brain development. While the origin of these effects is not well understood, it is known that anesthesia can disrupt oxygen regulation in the brain, which is critically important for maintaining healthy brain function. Here we investigated how anesthesia affected brain tissue oxygen regulation in neonatal rabbits by compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Our previous findings also point to hyperoxia as a potential risk factor during anesthesia delivery. Using direct electrode measurements of oxygen concentration, we found that anesthesia delivered in 80% oxygen greatly increased (by up to 300%) oxygen concentration in the cortex of neonates 18 . It is known that the generation of reactive oxygen species directly depends on the concentration of oxygen 30 and can lead to a variety of pathological effects in the brain 31 33 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous findings also point to hyperoxia as a potential risk factor during anesthesia delivery. Using direct electrode measurements of oxygen concentration, we found that anesthesia delivered in 80% oxygen greatly increased (by up to 300%) oxygen concentration in the cortex of neonates 18 . It is known that the generation of reactive oxygen species directly depends on the concentration of oxygen 30 and can lead to a variety of pathological effects in the brain 31 33 .…”
Section: Discussionmentioning
confidence: 92%
“…One such potential factor is the level of oxygen. In a previous study 18 we recorded a large increase of brain partial oxygen pressure during anesthesia, especially when combined with 80% oxygen, which has the potential to cause hyperoxic damage via the generation of reactive oxygen species 19 . Thus, we tested anesthesia delivery in air as well as in 80% oxygen to gauge the impact of oxygen on anesthesia-induced damage.…”
Section: Introductionmentioning
confidence: 95%
“…The dominant frequency of brain tissue oxygen oscillations (BTOO), which are attributed to vasomotion at the level of arterioles (Hudetz et al, 1998;Aalkjaer et al, 2011;Mateo et al, 2017), has been shown to change during development (Doubovikov and Aksenov, 2020). The dominant frequency of BTOO is around 1-2 cycles/min (0.0167-0.0333 Hz) in neonates (Aksenov et al, 2018) and approximately 10 cycles/min (0.167 Hz) in adults (Linsenmeier et al, 2016). Based on our findings, it is possible that neonatal anesthesia may disrupt normal developmental shift to higher frequency range of vasomotion, which could manifest as an increase in ALFF in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriolar vasomotion follows a typical developmental trajectory. In adults, it is characterized by a 10 cycles per minute (cpm) dominant power frequency ( 35 , 36 ), whereas underdeveloped vasomotion has a dominant frequency below 3 cpm ( 37 ). This shift in frequency of vasomotion and corresponding brain tissue oxygen oscillations represents a normal development and is needed to prevent localized hypoxia depending on the oxygen demand by developing neurons and neuronal networks ( 36 ).…”
Section: The Possible Relationship Between Anesthesia-induced Apoptotic Neurodegeneration Neurovascular Interactions and Fmrimentioning
confidence: 99%